Efficacy of alemtuzumab and natalizumab in the treatment of different stages of multiple sclerosis patients. Issue 8 (February 2018) - Wang, Li; Qi, Chun-Hui; Zhong, Ren; Yuan, Chao; Zhong, Qiu-Yue
Abstract: Background: Multiple sclerosis (MS) is an autoimmune disease, in which the insulating covers of nerve cells in the brain and spinal cord are demyelinated. This study was conducted to compare the efficacy of alemtuzumab and natalizumab in the treatment of different stages of MS patients. Methods: A total of 585 patients diagnosed with MS and hospitalized were included and analyzed after which they were divided into the primary progressive MS A and B groups, the relapsing-remitting MS (RRMS) C and D groups, and the secondary progressive MS E and F groups. Patients in A, C, and E groups were administered alemtuzumab while those in B, D, and F groups were administered natalizumab for the treatment. The expanded disability status scale (EDSS) scores and the EDSS difference were calculated before and after treatment. The number of head magnetic resonance imaging enhanced lesions in the patients, recurrence time and recurrence rate were measured before and after treatment. Results: The EDSS score of the RRMS group was significantly lower than that of the primary progressive MS group and the secondary progressive MS group. After 12 months of treatment, the EDSS score of RRMS patients treated with natalizumab was significantly lower compared with the patients with alemtuzumab, and the difference before and after treatment was significantly higher than alemtuzumab. The recurrence rate of the RRMS-D group was significantly lower than the RRMS-C group. After 12 months of treatment, compared with the RRMS-C group, a significant reduction was observed in the number of head magnetic resonance imaging enhanced lesions and longer recurrence time in the RRMS-D group. Conclusion: The efficacy of natalizumab was better than alemtuzumab in the treatment of patients in the RRMS group, while there was no significant difference among other stages of MS patients, which provided the theoretical basis and clinical guidance for the treatment of different stages of MS.